SUBJECT-VERB CONCORD WITH COLLECTIVE NOUNS OR THE COUNT-MASS DISTINCTION: WHICH IS MORE DIFFICULT FOR POLISH LEARNERS OF ENGLISH? - Dziemianko, Anna (Versita Ltd., de Gruyter, 2008)
Two aspects of English syntax were chosen for closer analysis in the present paper, i.e., subject- verb concord involving collective nouns in the singular and the syntactic marking of noun reclas- sification from the category of uncountable nouns to that of countable ones with the help of the indefinite article. The study aims to find out which of them is more difficult for Polish learners of English and whether the degree of difficulty depends on the learners’ proficiency in the foreign language. The discussion is based on the results yielded by an empirical study in which interme- diate and advanced Polish students of English took part. The subjects had to complete partial English translations of Polish sentences with specific low-frequency English nouns which substi- tuted true English equivalents of the Polish nouns shown in the sentences. The study reveals that marking subject-verb concord in the case of collective subject nouns was as difficult for the sub- jects as signaling the count-mass distinction by means of the indefinite article and the zero arti- cle, respectively.
Keywords: collective nouns; subject-verb concord; noun reclassification; articles